EVALUATION OF ANTI-PYRETIC ACTION OF NELAMUCHCHALA (GYMNOSTACHYAM FEBRIFUGUM BENTH.)-AN EXPERIMENTAL STUDY (AYUSHDHARA, 2017)
Folklore medicine is an integral part of Ayurveda. Nelamuchchala (Gymnostachyam febrifugum Benth.) is one such drug which is traditionally used for fever, ulcers, cough, metrorrhagia and puerperal fever. The objective of the study is evaluation of the anti-pyretic actions in albino rats. The healthy albino rats are selected and grouped into 5. The control, standard, trial into three in different dosage forms i.e., normal dose (1ml), half dose (0.5ml). double dose (2ml) The decoction of Trial drug prepared and given in the different dosage forms. Pyrexia or Fever is induced by using Brewer's Yeast solution injected subcutaneously at thigh region and temperature rise after 1hr. Then hourly temperature recorded upto 14 hours. Result obtained from the study was statistically analysed that standard, trail group in normal (p